Pengembangan Sistem Informasi Manajemen Pelanggan Android untuk Meningkatkan Layanan Air Bersih PDAM Sungai Lilin - Tegar Febrian; Karnadi Karnadi; Syarifah Aini (Lembaga Pengembangan Kinerja Dosen, 2025)
Customer service at PDAM Tirta Randik in Sungai Lilin District still faces several issues, such as delays in delivering billing information, manual data recording processes, and frequent input errors in customer data. Previous studies on PDAM information systems generally focused only on data recording or water flow monitoring, but have not provided an integrated solution for mobile-based customer management. This study presents a novelty in the form of an Android-based Customer Management Information System integrated with a server database, designed to provide real-time information access, automated billing generation, and monitoring of water usage history. The research employs a Research and Development (R&D) approach using the Software Development Life Cycle (SDLC) Waterfall model. The system was evaluated using: (1) black-box testing to validate system functionality; and (2) usability assessment using the System Usability Scale (SUS) to determine user acceptability. The results of black-box testing indicated that all features operated according to specifications. The SUS evaluation involving 20 respondents produced an average score of 82.5, categorized as “Excellent” with an acceptance level of Grade A. This information system can improve the accuracy of customer data recording, accelerate access to billing information, and enhance user satisfaction. It can serve as a reference model for the digitalization of PDAM services and has the potential for further development through the integration of digital payment features.